2007
DOI: 10.1097/01.min.0000295694.15470.1c
|View full text |Cite
|
Sign up to set email alerts
|

Do we discriminate?

Abstract: Men in nursing are the silent minority in our femaledominated profession. Male-dominated professions, such as engineering and medicine, are becoming more gender balanced, yet the ratio of males to females in some female-dominated professions have essentially remained unchanged over the past decades. 1 But why haven't the numbers grown? What factors impact men's recruitment and retention in nursing?Some claim that men in nursing struggle with stereotyped attitudes of their female counterparts. Men are stereotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…From this survey, nurses described several barriers, including lack of a mentorship program for male students, no male faculty and limited opportunity to work with men nurses in the clinical setting, and no information on the history of men in nursing. Crigger, Luckman, and Galusha () explored discriminatory attitudes and behaviors toward men as perceived by both male and female nursing students, and found that when these students were compared male students found their educational experience as sexist and discriminatory.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…From this survey, nurses described several barriers, including lack of a mentorship program for male students, no male faculty and limited opportunity to work with men nurses in the clinical setting, and no information on the history of men in nursing. Crigger, Luckman, and Galusha () explored discriminatory attitudes and behaviors toward men as perceived by both male and female nursing students, and found that when these students were compared male students found their educational experience as sexist and discriminatory.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Of the students who participated ( n = 221), in comparison with the women nursing students and the other non‐nursing university students, men nursing students reported being more affected by both sexism and discrimination within their program of study. Using a descriptive design, Crigger, Luckman, and Galusha (2007) in the United States were the first researchers to explore discriminatory attitudes and behaviors toward men as perceived by both men and women nursing ( n = 265) students. These students were completing a diploma, baccalaureate, or an associate degree program.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, hospital coordinators prefer female to male students for several reasons, such as their commitment and availability of clinical instructors. Hence, defining the capacity or number of students to be accepted into each hospital for both male and female nursing students is important in order to provide a fair opportunity for both genders for clinical training [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%